'The medical world is very good at cis people, but trans is a specialisation'. Experiences of transgender and non-binary people with accessing primary sexual and reproductive healthcare services in the Netherlands - Noor C. Gieles; Moo Zinsmeister; Sophie Pulles; Allis Harleman; Jason van Heesewijk; Maaike Muntinga (Taylor & Francis Group, 2023)
Transgender and non-binary (TNB) people are at increased risk of adverse sexual and reproductive health (SRH) outcomes compared to cisgender people. With this qualitative study, we investigated the experiences of TNB people with access to primary SRH care in the Netherlands. We conducted semi-structured, explorative interviews with fourteen TNB individuals. Data were analysed using thematic analysis. We identified three themes: 'navigating cisgender assumptions', 'depending on your healthcare provider' and 'access requires labour'. In primary SRH care, respondents felt that healthcare providers made incorrect assumptions about their care needs which required respondents to actively disclose their gender identity or medical history. However, some respondents felt disclosure also exposed them to clinical bias, or reduced them to a medical category 'transgender' that their healthcare providers perceived to require specialised knowledge. In this context, respondents felt the onus was on them to ensure their SRH care needs were met. Using the concept of trans erasure, we highlight how TNB people are put at risk of adverse SRH outcomes. Creating equitable care access requires not only that providers are educated on TNB health needs and their own cisnormativity, but also an ongoing, critical reflection on the use of gender- and sex-based categories in medicine.